Exploring Open Distance Learning at a Jordanian University: A Case Study - Dirani, Khalil M.; Yoon, Seung Won (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
This case study explores an open distance learning program offered by the Information Technology and Computing (ITC) department at AOUJ, a major university in Jordan. It provides an overview of e-learning in the Arab region and explores factors that affect ODL quality in the Arab Open University in Jordan (AOUJ). The research utilized a qualitative approach, which included five lengthy semi-structured interviews with the program director, two instructors, and three students. Three important conclusions can be drawn from the study about e-learning in the Arab region: (1) the existence of adverse conditions, (2) the presence of strong instructional practices, and (3) the need to improve administrative support.